2020
DOI: 10.3390/pathogens9020118
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Mussel (Mytilus galloprovincialis) as Intermediate Host for the Anisakid Sulcascaris sulcata (Nematoda), a Pathogen Parasite of the Mediterranean Loggerhead Turtle (Caretta caretta)

Abstract: Sulcascaris sulcata (Anisakidae), a pathogenic nematode of sea turtles, may cause ulcerous gastritis with different degrees of severity. Previous studies demonstrated a high prevalence of infection in the Mediterranean loggerhead turtle (Caretta caretta), although no data on the potential intermediate hosts of this nematode has been published thus far from the Mediterranean basin. Here, using molecular analyses, we demonstrated that the cross sections of nematode larvae observed histologically in Mediterranean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(32 reference statements)
0
5
1
Order By: Relevance
“…In fact, the presence of S. sulcata had been described in clams and scallops in Pretto et al [ 40 ] and Marcer et al [ 39 ] and according to Lazar et al [ 35 ] they represent the most frequent ingested bivalve molluscs for the Adriatic C. caretta . Conversely to Santoro et al [ 33 ] who examined some specimens of loggerhead sea turtle from the Sicilian coasts, in our samples we did not find any individual with these parasites. This apparent contrast could be explained by the scarcity of these molluscs (scallops, clams and mussels) in Sicily.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In fact, the presence of S. sulcata had been described in clams and scallops in Pretto et al [ 40 ] and Marcer et al [ 39 ] and according to Lazar et al [ 35 ] they represent the most frequent ingested bivalve molluscs for the Adriatic C. caretta . Conversely to Santoro et al [ 33 ] who examined some specimens of loggerhead sea turtle from the Sicilian coasts, in our samples we did not find any individual with these parasites. This apparent contrast could be explained by the scarcity of these molluscs (scallops, clams and mussels) in Sicily.…”
Section: Discussioncontrasting
confidence: 99%
“…According to Gracan et al [ 21 ] and Valente et al [ 30 ] this difference could be attributed to the feeding ecology or habitat preferences of C. caretta ; in fact, authors found [ 21 , 30 ] a different composition of the helminthic fauna during necropsies of individuals of C. caretta from different parts of the Mediterranean Sea and the Atlantic Ocean. This difference is also evidenced by the exclusive presence of the nematode S. sulcata in the individuals from the Adriatic Sea, previously reported by Manfredi [ 31 ], Scaravelli [ 32 ], Gracan [ 21 ], Santoro [ 33 ] and by the presence of the eggs of digenean Spirorchiidae, Hapalotrema sp. [ 4 ].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…However, knowledge concerning the first intermediate hosts of Anisakis and Hysterothylacium in Mediterranean waters is currently lacking. For Sulcascaris, bivalve molluscs and gasteropods serve as intermediate hosts in Mediterranean (Marcer et al, 2020;Santoro et al, 2020aSantoro et al, , 2022a. In particular, the Mediterranean scallop Pecten jacobeus and the queen scallop Aequipecten opercularis were recognized as intermediate hosts in the Adriatic Sea (Marcer et al, 2020).…”
Section: Chosen Tths Among Nematodes: Biodiversity and Ecologymentioning
confidence: 99%